Research Progress and Outlook of Food Grade Rice Bran - MA Zong-hui; YIN Bao-ru; ZHANG Hai; XU Xue-bing (Liang you shipin ke-ji, 2021)
This paper reviews the nutrition and utilization of rice bran and the future development of food grade rice bran. Rice bran has high nutritional value and rich biological activities. The utilization of rice bran fiber is mainly through modification. The combination of physical and enzymatic methods and supercritical CO2 treatment are beneficial to improve the soluble dietary fiber content and fiber extraction rate. The utilization of rice bran protein includes extraction and modification. The study of extraction of rice bran protein focuses on the combination of physical and enzymatic methods. Moreover, subcritical water, which is a new green extraction technology, has gradually become a research hotspot. The rice bran protein is mainly modified using enzymatic method to improve the function and biological activity of the protein. Therefore,studies on the development of food grade rice bran will be a trend in the future.